(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Based on an "imaginative operation" (Tavares, 2020), mojuba ara emerges as a decolonial exercise in summoning the embodied knowledges that constitute the afrodiaspora. Arguments were presented that demonstrate how colonization and modern western thought founded racist discourses about black bodies and knowledge. Finally, some examples from the field of Afrodiasporic dances demonstrated how they are permeated by values ​​such as ancestry and musicality, expressing unique conceptions of body and dance and justifying the need to revise the histories and curricula of the performing arts at all levels of Brazilian education, in light of our own experiences.